MODIFICATION OF CARBON PASTE ELECTRODE WITH MWCNT AND MOLECULARY IMPRINTED POLYMER FOR MALATHION ANALYSIS BY VOLTAMMETRY METHOD - Nazhifah, Naurah
Malathion (MAL) is a group of organophosphorus pesticides. However, the use of MAL with high concentrations or frequent frequency can trigger accumulation. MAL residue disturbs the human nervous system due to the inhibition of the performance of the acetylcholinesterase (AChE) enzyme. Therefore, it is necessary to do a quantitative analysis to determine the levels of MAL. In this study, the indirect voltammetry method was used to measure MAL. Indirect measurements were carried out by measuring probe solutions, namely K3Fe(CN)6 and K4Fe(CN)6 in an electrolyte solution of Phosphate Buffer Saline (PBS). The working electrode used is a modified carbon paste electrode MWCNT and MIP (EPK-MWCNT-MIP). MWCNTs were used to increase sensitivity, MWCNTs were characterized using PSA and a particle size distribution of 114 nm was known, which indicated that MWCNTs are nanoparticles. MIP is used to increase the selectivity of the measurement. MIP was synthesized using the bulk polymerization method using acrylic acid as a functional monomer, ethylene glycol dimethacrylate (EGDMA) as a crosslinker, acetonitrile as a porogen, and benzoyl peroxide (BPO) as an initiator. As a control for MIP, NIP synthesis was performed. NIP and MIP were characterized using SEM-EDX (Scanning Electron Microscopy – Energy Dispersive Xray), FTIR (Fourier Transform Infra Red), and PSA (Particle Size Analyzer). Based on the results of the SEM- EDS analysis, it is known that MIP contains Phosphorus (P) and Sulfur (S) atoms originating from MAL, while NIP does not contain P and S atoms. C- O and 1670-1760 cm-1 derived from C=O, from the functional monomer Acrylic acid and the crosslinker EGDMA. PSA analysis shows that the NIP particle size distribution is homogeneous, while the MIP is heterogeneous. Based on the characterization results, MIP was successfully synthesized. The measurement is based on measuring the current drop from the probe solution to the probe solution + Malation. Based on the results of the analysis, it is known that the optimum conditions for the measurements obtained include measurements using modified MWCNT and MIP electrodes (EPK-MWCNT-MIP) with a reduced current of 7.92 µA, with the optimum pH of the electrolyte solution being pH 7, and the optimum method